The 21st Century Metropolis: New Geographies of Theory (Andamios, Revista de Investigación Social, 2013)
This paper calls for “new geographies” of imagination and epistemology in the production of urban and regional theory. It argues that the dominant theorizations of global city-regions are rooted in the EuroAmerican experience and are thus unable to analyse multiple forms of metropolitan modernities. By drawing on the urban experience of the global South, the paper presents new conceptual vectors for understanding the worlding of cities, the production of space, and the dynamics of exurbanity. It makes the case that such area-based knowledge deepens recent theoretical attempts to articulate a relational study of space and place.
Keywords: New Geographies; Urban Futures; Urban Theory; Urbanization; Urbanism; Third World Cities